Digital smile design as a tool in the planning of porcelain laminate veneers restoration - Sávio Morato de Lacerda GONTIJO; Phelipe Marke MORGADO; Leniana Santos NEVES; Esdras Campos FRANÇA; Elizabeth Maria Bastos LAGES; Hugo Henriques ALVIM (RGO: Revista Gaúcha de Odontologia, 2021)
ABSTRACT Digital smile design is an important tool for esthetic planning in dentistry as it facilitates ease of communication between professionals and patients. This clinical report has the objective of describing a clinical procedure involving digital smile design for the placement of porcelain laminate veneer restorations. The digital smile design included dental and facial analyzes. The smile curve was drawn and a dental ruler was used to delimitate the spaces between each tooth. An approximate simulation of the smile was generated using Adobe Photoshop software. For esthetic and functional evaluation of the digital plan was created a diagnostic waxing and mock-up. The laminate veneers were made with feldspathic porcelain. Digital smile design was essential for successful planning because it enabled better patient contact with the end result. This case demonstrates the importance of this tool in esthetic dentistry.